The Development of Phonological System Made by the Children - Karisma E. Tarigan (BIRCU, 2019)
Language is one of the most important and difficult for young children in communication. Most children learn to talk in the years before school entry. The objective of this study is the writer tries to investigate and identify the phonological system made by children 3 years to 5 years old. The writer use descriptive qualitative analysis in order to figure out and identify the form of phonological and semantic system made by children at the age 3-5 years old. The writer use observation and interview in collecting the data. The research finding in this study were there are omission that can be seen in phonological system on children at the age 3-4 years, the consonant sound of /k/, /t/, /r/, and /s/ and there also replacement sound occurs in pronunciation made by the age 3-4 years such sound letter /c/ with /s/ and letter sound consonant /r/ with /l/. At the age of 5 years, the sound of consonant has been seen more clearly in the pronunciation of words. They have been able to recognize the sound of consonant /k/, /t/, /r/, and /s/. in conclusion, The phonological system made by children 3 years to 5 years old it can be seen from the difficulties of the latter sound; /t/, /d/, /r/, /l/, and the replace of position latter /s/ with /c/ and also the latter /r/ with /l/.